How Breast Cancer Patients Want to Search for and Retrieve Information From Stories of Other Patients on the Internet: an Online Randomized Controlled Experiment - Overberg, Regina; Otten, Wilma; Man, Andries de; Toussaint, Pieter; Westenbrink, Judith; Zwetsloot-Schonk, Bertie (JMIR Publications, 2010)
BackgroundOther patients' stories on the Internet can give patients information, support, reassurance, and practical advice. Objectives We examined which search facility for online stories resulted in patients' satisfaction and search success. Methods This study was a randomized controlled experiment with a 2x2 factorial design conducted online. We facilitated access to 170 stories of breast cancer patients in four ways based on two factors: (1) no versus yes search by story topic, and (2) no versus yes search by writer profile. Dutch speaking women with breast cancer were recruited. Women who gave informed consent were randomly assigned to one of four groups. After searching for stories, women were offered a questionnaire relating to satisfaction with the search facility, the stories retrieved, and impact of the stories on coping with breast cancer. Of 353 enrolled women, 182 (51.6%) completed the questionnaire: control group (n = 37), story topics group (n = 49), writer profile group (n = 51), and combination group (n = 45). Results Questionnaire completers were evenly distributed over the four groups (χ23 = 3.7, P = .30). Women who had access to the story topics search facility (yes vs no): were more positive about (mean scores 4.0 vs 3.6, P = .001) and more satisfied with the search facility (mean scores 7.3 vs 6.3, P < .001); were more positive about the number of search options (mean scores 2.3 vs 2.1, P = .04); were better enabled to find desired information (mean scores 3.3 vs 2.8, P = .001); were more likely to recommend the search facility to others or intend to use it themselves (mean scores 4.1 vs 3.5, P < .001); were more positive about how retrieved stories were displayed (mean scores 3.6 vs 3.2, P = .001); retrieved stories that better covered their information needs (mean scores 3.0 vs 2.6, P = .02); were more satisfied with the stories retrieved (mean scores 7.1 vs 6.4, P = .002); and were more likely to report an impact of the stories on coping with breast cancer (mean scores 3.2 vs 2.9, P =. 02). Three main effects were associated with use of the writer profile search (yes vs no): being more positive about (mean scores 3.9 vs 3.6, P = .005) and more satisfied with the search facility (mean scores 7.1 vs 6.5, P =. 01), and being more positive about how retrieved stories were displayed (mean scores 3.8 vs 2.9, P < .001). For satisfaction with the search facility, an interaction effect was found (P = .03): at least one of the two search facilities was needed for satisfaction. ConclusionsHaving access to the story topics search facility clearly had the most positive effect on patient satisfaction and search success.